Operational Management in Christian Theatre Productions: A Comparative Investigation of Zion Royal Theatre and Free Gift International (Integral Research, 2025)
With an eye towards Zion Royal theatre and Free Gift International, this study presents a comparison of operational management techniques in Christian theatrical production. Using a case approach, this study looks at how these companies deliberately use creative talent and resources to reach operational effectiveness. It highlights how these elements affect organizational performance by means of common difficulties faced by various theatre ministries and by means of an analysis of their management approaches, leadership styles, and audience involvement tactics. The study uses a mixed-methods approach combining quantitative and qualitative data collecting. Semi-structured interviews with three important stakeholders in every company yield qualitative data that offer in-depth operational dynamic insights. By means of stratified random sampling of 100 audience members each company using survey questionnaires, quantitative data are gathered, therefore providing a larger viewpoint on audience impressions. Organizational Effectiveness Theory (OET) and the Resource-Based View (RBV) provide the foundation of the study, therefore guaranteeing a strong theoretical framework. Results show that although both companies give audience involvement, spiritual messaging, and resource use top priority, their structure organization and leadership style match their particular operating environments. Providing useful insights for Christian theatre practitioners, the study contributes to the body of knowledge on organizational success and resource management in the creative sectors. It finishes with recommendations to better financial planning, optimize human resource allocation, integrate innovative technologies, expand marketing channels, and strengthen community engagement.  These ideas are presented as approaches to improve operational management, ensuring cultural, religious, and social relevance, and establishing sustainability in Christian theatre.
Keywords: Theatre, Management, Operational Management, Christian, Christian Theatre Productions, Organizational Structure, Financial Planning, Human Resource Allocation.